A Summary of Scientific Method - Kosso, Peter; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
No back cover text
Keywords: Philosophy (General).; Science (General).; Science -- Philosophy; Philosophy; Philosophy of Science; Science, general